A Chinese Patent Medicine JiaYanKangTai Alleviates Inflammatory Lesions of Experimental Autoimmune Thyroiditis by Regulating Interleukin-17 Signaling - Pan, Yajing; Zhang, Qiue; Zhang, Chengfei; Wu, Lili; Qin, Lingling; Liu, Tonghua; Hu, Kaiwen (Frontiers in Endocrinology, 2022)
Objective: This study was aimed to investigate the effects of JiaYanKangTai (JYKT) on regulating interleukin-17 (IL-17) signaling in rats with autoimmune thyroiditis. Methods: Lewis rats were administrated with JYKT for eight weeks after a seven-week subcutaneous injection of thyroglobulin with adjuvant and feeding iodine water. Ultrasonography was performed and total volume of thyroid was calculated. The expressions of autoantibodies and hormones were detected. Morphological changes of thyroid were observed. Metabolomics profile and metabolic network analysis were conducted. IL-17 signaling was detected by polymerase chain reaction and immunohistochemistry separately. Results: JYKT reduced the mean volumes of thyroid, decreased both levels of TPOAb and TGAb, and alleviated lymphocytic infiltration of the thyroid. Metabolic network analysis of metabolomics proved IL-17 signaling pathway as a critical pathway in JYKT administration for autoimmune thyroiditis. JYKT downregulated expressions of IL-17A, TRAF6, p-ERK1/2 and TNF-α. Conclusion: JYKT alleviated inflammatory lesions of experimental autoimmune thyroiditis by regulating IL-17 signaling